Small RNA Expression Profiling Reveals hsa-miR-181d-5p Downregulation Associated With TNF-α Overexpression in Sjögren’s Syndrome Patients - Castro, Isabel; Carvajal, Patricia; Jara, Daniela; Aguilera, Sergio; Heathcote, Benjamín; Barrera, María-José; Aliaga-Tobar, Víctor; Maracaja-Coutinho, Vinicius; Urzúa, Ulises; Quest, Andrew F. G.; González, Sergio; Molina, Claudio; et al. (Frontiers in Immunology, 2022)
MicroRNAs (miRNAs) are small non-coding RNAs (sRNA), that alter gene expression by binding to target messenger RNAs (mRNAs) and repressing translation. Dysregulated miRNA expression has been implicated in the pathogenesis of autoimmune diseases such as Sjögren’s syndrome (SS). The aim of this study was to characterize the global profile of sRNAs in labial salivary glands (LSG) from SS-patients and to validate potential miRNA candidates implicated in glandular inflammation. LSG from 21 SS-patients and 9 sicca controls were analyzed. A global next generation sequencing (NGS)-based sRNA profiling approach was employed to identify direct targets whereby differentially expressed miRNAs were predicted using bioinformatics tools. miRNA levels were validated by TaqMan and target mRNA levels were determined by quantitative real-time PCR. We also performed in vitro assays using recombinant TNF-α. NGS shows that ~30% of sRNAs were miRNAs. In comparison with samples from sicca controls, four miRNAs were found differentially expressed in LSG from SS-patients with low focus score (LFS) and 18 from SS-patients with high focus score (HFS). The miRNA with the most significant changes identified by NGS was hsa-miR-181d-5p and downregulation was confirmed by TaqMan analysis. Levels of TNF-α mRNA, a direct target of hsa-miR-181d-5p, were significantly increased and negatively correlated with hsa-miR-181d-5p presence. Moreover, positive correlations between TNF-α transcript levels, focus score, ESSDAI, and autoantibody levels were also detected. Furthermore, TNF-α stimulation decreased hsa-miR-181d-5p levels in vitro. Downregulation of hsa-miR-181d-5p in LSG from SS-patients could contribute to the glandular pro-inflammatory environment by deregulation of its direct target TNF-α. Further dissection of the pathophysiological mechanisms underlying the hsa-miR-181d-5p-mediated action in inflammatory conditions could be useful to evaluate the benefits of increasing hsa-miR-181d-5p levels for restoration of salivary gland epithelial cell architecture and function.